Stuttering and hearing loss - N, Rathna; NP, Nataraja (Journal of All India Institute of Speech and Hearing, 1972)
The story often been recounted of the American Indian who stood up to stutter a defiance to Wendell Johnson’s paper "The Indian’s have no word for it", at a conference of the American Speech and Hearing Association. Mention has also been made that after Robert West had hypothesized the impossibility of a diabetic stuttering a gentleman in the audience announced that he was a diabetic who stuttered. The Indian was a fake and was part of a practical joke ; the diabetic was not. The main point is that the exception proves that rule is a good repartee at casual conversation, but it is irrelevent in scientific explanations. It is important that any theory which tries to be comprehensive explains or at least takes note of the exceptions. The theory should not only include and explain exceptions to the theory directly but it should also explain exceptions to the inferences that are drawn directly from the theory. Thus the exceptions when explained helps to expand the pre-view of the theory or when it is not explained limits the scope and strength of the theory. While it is generally conceded that a theory works only within the limited framework in which it is formed, theories when propounded sound dangerously comprehensive. Therefore the exceptions become extremely important in challenging such postures of comprehensiveness.